An intelligent aid for the visually handicapped - Koh, Jacky (Nanyang Technological University, 2021)
Orientation is an important aspect of navigation. With the aid of a GPS, navigation between points of interest become possible. Unfortunately, commercially available navigational systems often do not work well indoors. The purpose of this report is to study and explore the implementation of existing navigational technologies for the blind. Firstly, we will study existing location tracking technology, as well as their methodologies. Next, we will explore the combination of existing methodology with other new, less established technology. This will cover the flaws of a traditional location tracking technology. I have proposed a navigation system that can operate indoors, thus enabling the visually handicapped to navigate in a foreign building independently. The application interface is designed specifically for the blind. As a mobile application, it is affordable for the blind as the infrastructure cost will be covered by the building management adopting this technology. The navigation system is a phone application, that uses iBeacon technology. The software, methodology, and hardware setup of this navigation system will be further discussed in this report. At the end of the project, a prototype of the mobile application is developed for use.